Control of base flows with micro jets - Ahmed Ali Baig, Maughal; Al-Mufadi, Farhad; Khan, Sher Afghan; Rathakrishnan, Ethirajan (Walter de Gruyter, 2011)
This paper presents the results of an experimental investigation carried out to control the base pressure in a suddenly expanded axi-symmetric passage. Active control in the form of micro jets was employed to control the base pressure. Air injection at four locations at the base, symmetric to the nozzle axis was used as the active control. The jet Mach numbers at the entry to the suddenly expanded duct studied were 1.87, 2.2 and 2.58. The area ratio of the present study was 2.56. The length-to-diameter ratio of the suddenly expanded duct varied from 10 to 1. Nozzles generating the above jet Mach numbers were operated with nozzle pressure ratio (NPR) in the range 3 to 11. In addition to base pressure, wall pressure field along the duct was also studied. It is found that the active control in the form of blowing through small orifices (micro jets) are effective in controlling the base pressure field. As high as 65 percent increase in base pressure was achieved for certain combination of parameters of the present study. Micro jets do not disturb the flow field in the enlarged duct.